GAD65 haplodeficiency conveys resilience in animal models of stress-induced psychopathology - Müller, Iris; Obata, Kunihiko; Richter-Levin, Gal; Stork, Oliver (Frontiers in Behavioral Neuroscience, 2014)
GABAergic mechanisms are critically involved in the control of fear and anxiety, but their role in the development of stress-induced psychopathologies, including post-traumatic stress disorder (PTSD) and mood disorders is not sufficiently understood. We studied these functions in two established mouse models of risk factors for stress-induced psychopathologies employing variable juvenile stress and/or social isolation. A battery of emotional tests in adulthood revealed the induction of contextually generalized fear, anxiety, hyperarousal and depression-like symptoms in these paradigms. These reflect the multitude and complexity of stress effects in human PTSD patients. With factor analysis we were able to identify parameters that reflect these different behavioral domains in stressed animals and thus provide a basis for an integrated scoring of affectedness more closely resembling the clinical situation than isolated parameters. To test the applicability of these models to genetic approaches we further tested the role of GABA using heterozygous mice with targeted mutation of the GABA synthesizing enzyme GAD65 (GAD65+/- mice), which show a delayed postnatal increase in tissue GABA content in limbic and cortical brain areas. Unexpectedly, GAD65(+/-) mice did not show changes in exploratory activity regardless of the stressor type and were after the variable juvenile stress procedure protected from the development of contextual generalization in an auditory fear conditioning experiment. Our data demonstrate the complex nature of behavioral alterations in rodent models of stress-related psychopathologies and suggest that GAD65 haplodeficiency, likely through its effect on the postnatal maturation of GABAergic transmission, conveys resilience to some of these stress-induced effects.